The Role of BPOM Regulations in the Supervision of HN Beauty Skincare Products: A Maqāṣid Sharīʻah Perspective - Susanti Wulandari Putri; Ismail Yahya (MAQASIDI: Jurnal Syariah dan Hukum, 2026)
The widespread circulation of illegal cosmetic products in Indonesia, including HN (Hetty Nugrahati) Beauty Skincare which lacks official registration, poses serious threats to consumer safety and creates structural imbalance between business actors and the public. The regulatory framework encompassing Law No. 8 of 1999, Law No. 17 of 2023, Presidential Regulation No. 80 of 2017, and BPOM Regulation No. 23 of 2019 collectively establishes a comprehensive normative ecosystem for consumer protection in the cosmetics sector. This study employs a normative legal research method utilizing statute and conceptual approaches, drawing upon primary, secondary, and tertiary legal materials gathered through library research and analyzed through descriptive-prescriptive qualitative techniques. Findings reveal that BPOM’s pre-market and post-market supervisory mechanisms still face significant implementation gaps, evidenced by the discovery of 235 illegal cosmetic items valued at over IDR 8.91 billion in late 2024. The maqāṣhidh syarī’ah perspective reinforces the legitimacy of such supervision through two principal tenets, namely ḥifẓ al-nafs (preservation of life) and ḥifẓ al-māl (preservation of wealth), affirming that consumer protection constitutes not merely a juridical obligation but also a moral imperative within Islamic jurisprudence. It is concluded that Indonesia’s normative foundation for cosmetic consumer protection is already robust from both legal systems, yet demands substantial reinforcement at the implementation level.